Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Investasi - Zebua, Junar Cristin; Husna, Dhea Afri; Samosir, Marini Ibrani; Malau, Yois Nelsari; Mustafa, Mustafa (Universitas Gorontalo, 2023)
The research aimed to examine both simultaneously and partially the factors influencing investment decisions in food and beverage sector companies listed on the Indonesia Stock Exchange from 2018 to 2021 using multiple linear regression analysis. The test results found that profitability, liquidity, leverage, solvency, and company size variables simultaneously had a significant impact on investment decisions. In partial testing, profitability had no significant effect on investment decisions, liquidity had no significant effect on investment decisions, leverage had no effect but had a significant impact on investment decisions, solvency had no effect but had a significant impact on investment decisions, and company size had no significant effect on investment decisions.